A multi-faceted approach to unravel coding and non-coding gene fusions and target chimeric proteins in ataxia - Gullulu, Omer; Ozcelik, Emrah; Tuzlakoglu Ozturk, Merve; Karagoz, Mustafa Safa; Tazebay, Uygar Halis (Taylor & Francis Inc, 2025)
Ataxia represents a heterogeneous group of neurodegenerative disorders characterized by a loss of balance and coordination, often resulting from mutations in genes vital for cerebellar function and maintenance. Recent advances in genomics have identified gene fusion events as critical contributors to various cancers and neurodegenerative diseases. However, their role in ataxia pathogenesis remains largely unexplored. Our study Hdelved into this possibility by analyzing RNA sequencing data from 1443 diverse samples, including cell and mouse models, patient samples, and healthy controls. We identified 7067 novel gene fusions, potentially pivotal in disease onset. These fusions, notably in-frame, could produce chimeric proteins, disrupt gene regulation, or introduce new functions. We observed conservation of specific amino acids at fusion breakpoints and identified potential aggregate formations in fusion proteins, known to contribute to ataxia. Through AI-based protein structure prediction, we identified topological changes in three high-confidence fusion proteins-TEN1-ACOX1, PEX14-NMNAT1, and ITPR1-GRID2-which could potentially alter their functions. Subsequent virtual drug screening identified several molecules and peptides with high-affinity binding to fusion sites. Molecular dynamics simulations confirmed the stability of these protein-ligand complexes at fusion breakpoints. Additionally, we explored the role of non-coding RNA fusions as miRNA sponges. One such fusion, RP11-547P4-FLJ33910, showed strong interaction with hsa-miR-504-5p, potentially acting as its sponge. This interaction correlated with the upregulation of hsa-miR-504-5p target genes, some previously linked to ataxia. In conclusion, our study unveils new aspects of gene fusions in ataxia, suggesting their significant role in pathogenesis and opening avenues for targeted therapeutic interventions.Communicated by Ramaswamy H. Sarma
Keywords: Ataxia; gene fusion; RNA-Seq; fusion breakpoint; drug screening; peptide screening; miRNA sponging; non-coding fusion RNA; gene expression